Perlindungan dan Tanggung Jawab Hukum Karyawan Notaris sebagai Saksi Instrumenter dalam Akta Notaris (Studi Kasus Putusan No. 773/Pid.B/2021, Putusan No. 1209 K/Pid/2022, dan Putusan PK No. 39 PK/Pid/2025) - Wahyu Kurniawan; M. Yamani; Emelia Kontesa (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the legal protection afforded to notary employees acting as instrumentary witnesses in the preparation of authentic deeds and to examine the legal responsibilities borne by notaries under the Notary Office Act (Undang-Undang Jabatan Notaris—UUJN). This study employs a normative juridical method using statutory, conceptual, and case approaches through an analysis of the Semarang District Court Decision No. 773/Pid.B/2021, the Supreme Court Decision No. 1209 K/Pid/2022, and the Judicial Review Decision No. 39 PK/Pid/2025.The findings reveal that instrumentary witnesses perform a purely administrative and formal function in assisting the notary to fulfill procedural requirements of the deed, without authority to assess or bear responsibility for the material truth of the parties’ statements. Legal responsibility for the substance of the deed lies entirely with the notary as a public official, as stipulated in Articles 16 and 38 of the UUJN. Judicial analysis demonstrates a shift toward clearer separation between the notary’s professional responsibility and the role of notary employees as instrumentary witnesses.This study concludes that legal protection for instrumentary witnesses is an essential element of the notarial system to prevent misattribution of liability and excessive criminalization of notary employees. Strengthening regulatory frameworks, improving standard operating procedures within notary offices, and enhancing legal understanding among law enforcement officers are necessary to ensure consistency with the UUJN.